2015
DOI: 10.1007/s11306-015-0773-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic research on the role of interleukin-4 in Alzheimer’s disease

Abstract: Abstract:Inflammation plays a prominent role in the pathogenesis of Alzheimer's disease, affecting both brain and the peripheral system. Thus, modulation of inflammation in animal models of this neurodegenerative disorder may be of great interest to elucidate the pathological mechanisms underlying this inflammatory component. To this end, a metabolomic investigation on a triple transgenic mouse model obtained by crossing the APP/PS1 mice with interleukin-4 knockout mice (a model of impaired immune function) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 61 publications
7
20
0
Order By: Relevance
“…Thereby, metabolomic analysis of brain samples has been extensively applied to examine neurochemical perturbations involved in pathological mechanisms occurring in AD, in both humans 33,34 and transgenic mice. 17 Furthermore, previous metabolomic investigations in different biological compartments of this transgenic model showed numerous metabolic alterations, similar to those described in Tables 2-4, affecting brain 18,19 and serum samples. For this reason, the aim of this work was the characterization of the hepatic and renal metabolomic profiles in the APP/PS1 model of AD for the evaluation of possible implications of these metabolically active organs in the development of disease.…”
Section: Biological Meaningsupporting
confidence: 63%
See 2 more Smart Citations
“…Thereby, metabolomic analysis of brain samples has been extensively applied to examine neurochemical perturbations involved in pathological mechanisms occurring in AD, in both humans 33,34 and transgenic mice. 17 Furthermore, previous metabolomic investigations in different biological compartments of this transgenic model showed numerous metabolic alterations, similar to those described in Tables 2-4, affecting brain 18,19 and serum samples. For this reason, the aim of this work was the characterization of the hepatic and renal metabolomic profiles in the APP/PS1 model of AD for the evaluation of possible implications of these metabolically active organs in the development of disease.…”
Section: Biological Meaningsupporting
confidence: 63%
“…The analysis of brain samples from APP/PS1 and wild-type mice studied in this work has been previously performed using the same metabolomic multi-platform based on GC-MS and RP-UHPLC-MS, 18 as well as by using direct infusion mass spectrometry. 19 These studies demonstrated that hippocampus and cortex are the most perturbed brain regions in this transgenic model, but cerebellum, striatum and olfactory bulbs are also affected to a lesser extent. The comparison of metabolite profiles from liver, kidney and brain regions showed similar alterations in numerous compounds, thus demonstrating the systemic nature of pathological mechanisms underlying these metabolic abnormalities.…”
Section: Comparison With Brain Alterationsmentioning
confidence: 87%
See 1 more Smart Citation
“…Free cholesterol is usually detected in lipophilic extracts as a very intense signal at m/z 369. 35 adducts (m/z 404.39) is possible when ammonium salts are added to sample extracts, as described for glycerolipids. Similarly, cholesteryl esters (CE) are also exclusively detected by ESI(?…”
Section: Cholesterol and Derivativesmentioning
confidence: 99%
“…Particularly, the use of direct MS platforms has previously been described in a few research articles with the aim to elucidate pathological hallmarks associated with AD development and progression, in both human cohorts and transgenic animal models, as briefly discussed in this section. The methodology optimized by González-Domínguez et al, based on a two-step extraction procedure and subsequent DI-ESI-MS fingerprinting of serum samples, was successfully employed to identify discriminant metabolites between AD patients and healthy control subjects [16,33], as well as between various transgenic mice lines and wildtype littermates [34,35]. These studies revealed significant disturbances in the homeostasis of various lipid classes (e.g., phospholipids, fatty acids, glycerolipids), energy-related metabolites, neurotransmitters, and other metabolites, thus evidencing the utility of simple and easily available serum samples in clinical research.…”
Section: Application Of Dims Metabolomicmentioning
confidence: 99%